2016
DOI: 10.1517/14728222.2016.1162295
|View full text |Cite
|
Sign up to set email alerts
|

Nav1.7 and other voltage-gated sodium channels as drug targets for pain relief

Abstract: Introduction: Chronic pain is a massive clinical problem. We discuss the potential of subtype selective sodium channel blockers that may provide analgesia with limited side effects. Areas covered: Sodium channel subtypes have been linked to human pain syndromes through genetic studies. Gain of function mutations in Nav1.7, 1.8 and 1.9 can cause pain, whilst loss of function Nav1.7 mutations lead to loss of pain in otherwise normal people. Intriguingly, both human and mouse Nav1.7 null mutants have increased op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
155
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 186 publications
(157 citation statements)
references
References 71 publications
1
155
0
1
Order By: Relevance
“…In the transcriptome of sensory neurons from Advillin-Cre Na V 1.7 knockout mice, no changes in endogenous opioid receptor transcripts were reported, only upregulation of Penk mRNA and Met-Enkephalin protein21. It therefore appears that Na V 1.7 inhibition in combination with opioid receptor activation, whether through upregulation of endogenous opioids, such as the enkephalins as demonstrated in the knockout experiments, or administration of exogenous opioids, as described here, can elicit profound analgesia53. Opioid receptors are expressed on peripheral sensory neurons, both on the peripheral and central projections, as well as along the axon, where they are involved in regulating neuronal excitability, action potential propagation, and neurotransmitter release through inhibition of calcium currents5455.…”
Section: Discussionmentioning
confidence: 50%
“…In the transcriptome of sensory neurons from Advillin-Cre Na V 1.7 knockout mice, no changes in endogenous opioid receptor transcripts were reported, only upregulation of Penk mRNA and Met-Enkephalin protein21. It therefore appears that Na V 1.7 inhibition in combination with opioid receptor activation, whether through upregulation of endogenous opioids, such as the enkephalins as demonstrated in the knockout experiments, or administration of exogenous opioids, as described here, can elicit profound analgesia53. Opioid receptors are expressed on peripheral sensory neurons, both on the peripheral and central projections, as well as along the axon, where they are involved in regulating neuronal excitability, action potential propagation, and neurotransmitter release through inhibition of calcium currents5455.…”
Section: Discussionmentioning
confidence: 50%
“…These include, in particular, subtype selective sodium channel-blocking agents, particularly Na v 1.7 antagonists 114 , and EMA401, a novel angiotensin type II antagonist that has been found to be effective in a phase II clinical trial in postherpetic neuralgia 115 . Although still in the preclinical phase, studies show promising results of stem cell treatment for neuropathic pain 116,117 .…”
Section: Managementmentioning
confidence: 99%
“…The mechanism of action of these substances, however, may not be completely clear as it has also been recently demonstrated that strong antagonism of Na V 1.7 activity leads to strongly increased expression of opioid peptide levels, which may contribute to the analgesic effects of loss of Na V 1.7 function. Whatever their precise mechanism, several of these substances have entered the drug development pipeline (for recent review, see [30]).…”
Section: Ion Channelsmentioning
confidence: 99%